Hit & stay - Cyzyk, Skizz; Tropea, Joe; Haricot Vert Films; Soundview Media Partners ([Baltimore, Md.] : Haricot Vert Films, 2013)
A documentary about priests and nuns who protested the Vietnam War by breaking into draft boards, destroying draft records, and then waiting around to be arrested. Their actions inspired a movement, which shaped the anti-war movement and helped bring an end to the draft.
Originally released as a motion picture in 2012.
Cinematographer and editor, Skizz Cyzyk ; music
In English.
Winner of Audience Choice Award, at the Chicago Underground Film Festival 2013
Winner of an Award, at the Sidewalk Film Festival 2013: Best Documentary
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 20, 2019)
Keywords: Civil disobedience -- United States -- History -- 20th century; Government, Resistance to -- United States -- History -- 20th.; Peace movements -- United States -- History -- 20th century; Vietnam War, 1961-1975 -- Draft resisters -- United States; Vietnam War, 1961-1975 -- Protest movements -- United States; Vietnam War, 1961-1975 -- Conscientious objectors -- Maryland -- Catonsville; Government, Resistance to -- United States; Trials (Conspiracy) -- New Jersey -- Camden; War -- Religious aspects -- Catholic Church; Catonsville Nine-Milwaukee Fourteen Defense Committee; Documentary films; Feature films; Nonfiction films; Internet videos; Streaming video